Bundled Innovations for Sustainable Technology Adoption Among Smallholder Farmers - Jizorkuwie, Abdul; Masoud, Jalaludeen; Amankwaa-Yeboah, Particia; Ofosu-Ampong, Kingsley; Worku, Wuletawu Abera (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Low adoption of agricultural innovations remains a major barrier to productivity and sustainability among smallholder farmers in Ghana. This report presents the establishment of on-farm demonstrations that bundled several innovations into a single practical package as Improved Technology Package. The package comprised site-specific fertilizer recommendations (SSF), fertilization at planting, climate-smart maize varieties, and simple mechanization tools such as a push planter and fertilizer applicator, to serve as enablers of adoption. This project aims to address key agronomic, labour, and resource challenges with a bundled package. The experiments were carried out in the Northern and Upper West regions under rainfed conditions. Researchers established the demonstrations with farmers and extension agents. The demonstrations consisted of two technologies, improved technology package and farmer practice to demonstrate to farmers the advantages of adopting the improved technology package. Farmers were also selected in each research community to replicate the improved package on their farms. Data was collected and analysed for both demonstration plots and farmer-replicated plots. ANOVA was used to analyze and separate the means on grain and biomass yield at a 5 percent level of significance. Results showed that the Improved Technology Package led to a significant increase in grain yield, with an average yield of 4,722 kg ha-1 compared to 2,826 kg ha-1 average yield from Farmer Practice plots. The average yield of 3292 kg ha-1 realized by farmers who replicated the package on their respective farms was more than twice the regional average of 1600kg ha-1. The Improved Technology Package led to precision, decreased labour burden and overall nutrient uptake. The results show that bundling innovations with implementation enablers can be valuable in bridging yield gaps.